Strategi Komunikasi Marketing Beeme Dalam Meningkatkan Brand Awareness Selama Event Imbex - Muhammad Yassin; Sari Ekowati (Tamilis Synex: Multidimensional Collaboration, 2026)
The increasing competition in Indonesia's skincare industry encourages companies to implement integrated marketing communication strategies to strengthen brand awareness and create positive brand experiences. This study aims to analyze the implementation of Integrated Marketing Communication (IMC) by PT Beeme Nusantara in building brand awareness and brand experience through its participation in the Indonesia Maternity, Baby & Kids Expo (IMBEX). This research employed a qualitative descriptive approach. Data were collected through semi-structured interviews with the Marketing Team, Event Person in Charge (PIC), and Brand Representatives, supported by observation and documentation. Data were analyzed using the interactive model of Miles, Huberman, and Saldaña, while data validity was ensured through source and method triangulation. The findings indicate that PT Beeme Nusantara implemented an integrated IMC strategy through coordinated activities before, during, and after the event by combining advertising, social media, public relations, sales promotion, event marketing, direct marketing, mobile marketing, and personal selling. The implementation of these integrated communication activities contributed to improving brand awareness, reflected in brand recognition, brand recall, and the potential to achieve top-of-mind awareness. Furthermore, direct interactions during the event successfully created positive brand experiences through sensory, emotional, cognitive, behavioral, and relational dimensions. The study concludes that the effectiveness of IMC is determined not only by the use of multiple communication channels but also by the consistency of marketing messages and the integration of consumer experiences across all customer touchpoints. These findings contribute to the development of integrated marketing communication studies, particularly within the skincare industry targeting mothers and children.